Global Observations of the Short‐Term Disturbances in the Geomagnetic Field and Induced Currents During the Supersubstorms Events of Solar Cycle 24 - Sritam Hajra; Nirvikar Dashora; J. Solomon Ivan (Space Weather)
Abstract Four supersubstorms of the solar cycle 24 are analyzed to investigate the global variations in the H‐component and geomagnetically induced currents (GICs). The response to the storm sudden commencement (SSC) of the 2012 and 2017 events is observed differently over different latitude bands. Initially, the latitude band of 0°–45° shows a step‐like preliminary positive impulse (PPI), 45°–65° shows a Gaussian‐kind of PPI and 65°–90° shows a preliminary reverse impulse, followed by a main impulse all over. The H‐component variations during the supersubstorm periods show a strong north‐south asymmetry over the high latitudes which is attributed to the seasonal dependence of the growth and decay of ionospheric currents respectively in the summer and winter hemispheres. The co‐latitude band of ∼55°–65° shows a complete reversal of phase (i.e., global positive peak) of the H‐component compared to the maximum depression observed from the close‐by latitude bands and peak depressions in the SYM‐H, SML, and AE indices. The low latitude variations exhibit a dominant local time‐dependent control of the perturbation electric fields over the short and long terms during the geomagnetic events. The D‐component variations reflect complex ionospheric contributions during the SSC and the main phase with more asymmetries and variability. The GIC threat represented by the dB/dt peaks during the supersubstorms shows the highest magnitude (∼900 nT/min) in the latitude band of 60°–75° with a secondary peak over the dip equatorial regions. Further, some scattered and prominent peaks over the mid and high latitudes outside the supersubstorm periods are also observed.